Active Learning Management in Islamic Education: Implementation of Pjbl, PBL, and Inquiry to Improve the Quality of Learning and Internalize Islamic Values - Yeni Sri Amriani; Murti Affiriani Hasibuan; Mahyiddin Mahyiddin; M.Fadli Fadli (Universitas Muhammadiyah Sumatera Utara, 2026)
This study examines the management of active learning in Islamic Religious Education (PAI) through the integrated implementation of three learning models: Project-Based Learning (PjBL), Problem-Based Learning (PBL), and Inquiry Learning. Using a conceptual-analytical approach to library research, this study identifies a significant research gap in the literature: the absence of an active learning management framework that integrates all three models at once along with the dimension of holistic internalization of Islamic values. The results of the study show that: (1) systematic PAI active learning management including planning, organizing, implementing, and evaluating is a prerequisite for the successful implementation of active models; (2) PjBL, PBL, and Inquiry each make a unique contribution to the development of students' cognitive, affective, and psychomotor competencies according to the goals of Islamic education; (3) the internalization of Islamic values takes place through three successive stages: cognitive understanding, affective appreciation, and psychomotor practice; and (4) portfolio-based authentic evaluation, observation, and reflection are the most appropriate instruments to measure the success of PAI active learning as a whole. This study recommends integrating an Islamic value-based active learning management framework into the curriculum, teacher training, and Islamic education policy in Indonesia.